Pembelajaran Mendalam dan Growth Mindset dalam Pendidikan Matematika: Systematic Narrative Literature Review - Khadijah (GENIUS: Jurnal Inovasi Pendidikan dan Pembelajaran, 2025)
This study examines the integration of growth mindset and deep learning in mathematics education through a Systematic Literature Review (SLR) guided by the PRISMA framework. Literature searches in Scopus, Web of Science, ERIC, and Google Scholar identified 74 initial studies. After title–abstract screening, full-text eligibility assessment, and inclusion–exclusion filtering, 22 studies met the criteria for synthesis. Data analysis employed extraction procedures, thematic coding, and thematic synthesis. Three main themes emerged. First, the growth mindset acts as a psychological foundation for deep learning through mechanisms of self-regulation and academic control. Second, its effectiveness is shaped by contextual factors such as socioeconomic inequality, teacher expectations, and academic support. Third, educational technologies (AI, ICT, maker education) enhance deep learning when paired with adaptive mindsets and supportive learning environments. The review concludes that effective integration of growth mindset and deep learning requires a reflective, inclusive, and supportive learning environment